2010
DOI: 10.1175/2009jas3334.1
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Mixing in the Extratropical Tropopause Region in a High-Vertical-Resolution GCM. Part II: Relative Importance of Large-Scale and Small-Scale Dynamics

Abstract: The relative roles of atmospheric motions on various scales, from mesoscale to planetary scale, in transport and mixing in the extratropical tropopause region are investigated using a high-vertical-resolution general circulation model (GCM). The GCM with a vertical resolution of about 300 m explicitly represents the propagation and breaking of gravity waves and the induced transport and mixing. A downward control calculation shows that the Eliassen-Palm (E-P) flux of the gravity waves diverges and induces a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…The isentropic diffusion coefficient K yy can be derived from the eddy meridional flux and meridional potential vorticity (PV) gradient on isentropic surfaces (Tung, 1986;Newman et al, 1988;Bartels et al, 1998;Miyazaki and Iwasaki, 2005;Miyazaki et al, 2010b) by neglecting the influence of slant diffusion:…”
Section: Eddy Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…The isentropic diffusion coefficient K yy can be derived from the eddy meridional flux and meridional potential vorticity (PV) gradient on isentropic surfaces (Tung, 1986;Newman et al, 1988;Bartels et al, 1998;Miyazaki and Iwasaki, 2005;Miyazaki et al, 2010b) by neglecting the influence of slant diffusion:…”
Section: Eddy Mixingmentioning
confidence: 99%
“…In the K yy estimation, steady conservative wave motions projected onto a meridional plane can cause apparent diffusion in addition to the true diffusion caused by dissipative wave motions, which may lead to significant differences between the estimated K yy and the true eddy mixing. In order to reduce this effect in our estimates, a time-averaging window t is applied to the eddy PV flux, as in Miyazaki and Iwasaki (2005) and Miyazaki et al (2010b). As a result, we expect that the estimated K yy will provide information on eddy mixing characteristics similar to estimates of the effective diffusivity (Nakamura, 1996;Haynes and Shuckburgh, 2000).…”
Section: Eddy Mixingmentioning
confidence: 99%
“…The mechanisms for formation of the TIL have not been determined, but both dynamical processes and radiative effects of O 3 and H 2 O variations may be involved (e.g., Randel et al, 2007c;Kunz et al, 2009;Miyazaki et al, 2010a). Observational Kunz et al, 2009) and model (Miyazaki et al, 2010b) results indicate a relationship between the TIL and processes in the ExTL; the details of this relationship and the role of the TIL in transport and mixing across the tropopause are only beginning to be explored. The lower panels of Fig.…”
Section: Characterization Of Dynamical Fields With Respect To the Jetsmentioning
confidence: 99%
“…The tropopause inversion layer (TIL) was proven to have impacts on the vertical propagation of atmospheric waves and eventually influences the dynamical and thermal structures of the middle and upper atmosphere [Birner, 2006;Bian and Chen, 2008;Grise et al, 2010;Miyazaki et al, 2010]. The TIL is a relatively new observational feature, which was first introduced by Birner et al [2002] and Birner [2006], and as yet no final explanation for TIL formation is available.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most previous studies on TIL focused on the climatology or formation mechanisms of the TIL, and only a few studies have reported the relationship between the TIL and the IGW [Birner, 2006;Miyazaki et al, 2010;Kunkel et al, 2014]. Birner [2006] suggested that TIL may influence the gravity wave propagation.…”
Section: Introductionmentioning
confidence: 99%